Imaging of myocardial inflammation with somatostatin receptor based PET/CT — A comparison to cardiac MRI. (1st September 2015) - Lapa, Constantin; Reiter, Theresa; Li, Xiang; Werner, Rudolf A.; Samnick, Samuel; Jahns, Roland; Buck, Andreas K.; Ertl, Georg; Bauer, Wolfgang R.
Abstract: Background: Acute myocarditis as well as post-ischemic myocardial inflammation are generally associated with a profound activation of the immune system. Current established imaging techniques such as cardiac MRI reliably demonstrate signs of acute myocardial injury. However, detection of mediating cells such as macrophages is currently limited to experimental settings. We aimed to investigate the feasibility of somatostatin receptor (SSTR) based positron emission tomography/computed tomography (PET/CT) for detecting inflammatory lesions in patients after acute myocardial infarction or acute peri-/myocarditis. Methods: 12 patients with active peri-/myocarditis (n = 6) or sub-acute myocardial infarction (n = 6) underwent SSTR-PET/CT and cardiac MRI within 3–10 days after onset of symptoms. The AHA 17-segment model of the left myocardium was used for visual localization of inflamed myocardium for both imaging modalities. Tracer uptake of infarcted/inflamed myocardium was assessed as mean and maximum standardized uptake value (SUVmean and SUVmax ) and compared with both remote myocardium and left ventricular (LV) cavity. Results: SSTR-PET/CT revealed areas with increased cardiac tracer uptake in all patients. In the 17-segment model, PET/CT yielded 55 and MRI 47 positive segments. Overall, concordance of the 2 modalities was 85.3% (174/204 segments analyzed). In 9.3% (19/204), more positive segments were identified by PET/CT, whereas in 5.4% (11/204), MRI detected more positive segments. Conclusions: The imaging patterns of SSTR-directed radiotracers and MRI in vivo show a close spatial relation of macrophage concentration and structural changes. This suggests the possibility of a new potential biomarker that predicts cardiac remodeling and, hence, progression towards heart failure. Prospective trials are warranted.